A review on mitigation of the DDoS Attack in cloud in regulated environment - Asia Ayaz Andrabi, Syed; Pandey, Sachi; Nazir, Akthar (International Journal of Engineering and Technology, 2018)
Distributed Denial of Service (DDoS) attacks are aimed at exhausting various resources of victim hosts, thereby preventing legitimate usage of their computational capabilities. In this paper, a proper and systematic mitigation technique presented to mitigate the DDoS attack in cloud environment. A robust mechanism is presented which consists of software based puzzle generation method to validate the real customer of cloud services provider from non-reals’ ones to provide better DDoS attack mitigation solution.